PENGEMBANGAN PREPARASI NANOPARTIKEL THYMOQUINONE-KITOSAN DENGAN METODE KOSOLVEN MENGGUNAKAN ISOPROPIL ALKOHOL - Binarjo, Annas; Yuwono, Tedjo; Priyanti, Renny (Universitas Ahmad Dahlan, 2015)
Thymoquinone, an active compound isolated from black cumin seeds (Nigella sativa L.), has pharmacological activity as anticancer, antiinflammatory, and immunomodulator. This compound has a volatile nature, easily oxidized, and low melting point, leading to difficulties in tablet formulation. Moreover, its low solubility in water leading to low bioavailability. Therefore, it is necessary to develop nanoparticle drug delivery systems to solve these problems. Chitosan-thymoquinone nanoparticles can be formed using sodium tripolyphosphate as cross linker by cosolven method. Chitosan solution in acetate buffer pH 4 was added to thymoquinone solution in 50%, 75%, 100% isopropyl alcohol, than sodium tripoliphosphate solution in water was added slowly in a gently stirrer.Â The nanoparticle produced was characterized in its loading capacity (LC), particle morphology, particle size, and zeta potential, as well as the loading efficiency (LE) of nanoparticle. Factorial Design Optimization resulted that the best condistion is achieved by 75% isopropyl alcohol using thymoquinone level of 10 mg/mL and chitosan level of 10 mg/mL. In this condition, the nanoparticle has LC of 8.71%, LE of 76.29%, 609.8 nm in diameter and zeta potential of 137.9 mV. It can be concluded that isopropyl alcohol can help the formation of nanoparticles thymoquinone. The particle size and zeta potential is too big, therefore it is craved to modify the process by variation in thymoquinone, chitosan, and sodium tripoliphosphat concentration.